2018
DOI: 10.1212/wnl.0000000000005057
|View full text |Cite
|
Sign up to set email alerts
|

Neurogranin as a predictor of memory and executive function decline in MCI patients

Abstract: High CSF Ng associates with poor memory scores in participants with MCI cross-sectionally and with poor memory and executive function longitudinally. The association of Ng with cognitive measures disappears when tau and Aβ are included in the statistical models. Our findings suggest that CSF Ng may serve as a biomarker of cognition. Synaptic dysfunction contributes to cognitive impairment in early-stage AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 33 publications
2
37
1
Order By: Relevance
“…One possibility is that changes in cognitive composites may be more difficult to detect but are less confounded by measurement errors and are therefore more robust when detected. In longitudinal studies, NG has been observed to predict conversion from MCI to frank AD dementia, raising the possibility that increased NG is a robust predictor of cognitive decline only later in the disease course [34] , [35] . In partial support of this hypothesis, NG has also been associated with longitudinal cognitive decline, but only in amyloid-positive individuals [8] .…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that changes in cognitive composites may be more difficult to detect but are less confounded by measurement errors and are therefore more robust when detected. In longitudinal studies, NG has been observed to predict conversion from MCI to frank AD dementia, raising the possibility that increased NG is a robust predictor of cognitive decline only later in the disease course [34] , [35] . In partial support of this hypothesis, NG has also been associated with longitudinal cognitive decline, but only in amyloid-positive individuals [8] .…”
Section: Discussionmentioning
confidence: 99%
“…Postmortem studies have shown that the full-length Ng is reduced in the parietal and temporal cortex in AD patients and processed into smaller peptides measurable in CSF reflecting synaptic degeneration [24]. CSF Ng levels are elevated in both AD and mild cognitive impairment (MCI) compared to healthy controls and associated with lower cognitive function and deterioration of white matter tracts and predict cognitive decline as well as conversion from MCI to AD [25][26][27][28][29][30][31][32][33][34][35][36]. No other published study has to our knowledge investigated the association between Ng and NPS.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, neurogranin level is a predictor of the progressive decline of memory and executive function in patients with MCI, but not in elderly control subjects, indicating a potential disease-specific effect. 9 In support of this idea, CSF neurogranin was found to increase gradually in a normal elderly population without cognitive impairments, but did not change in patients with MCI or AD, which suggests that this is an early indicator. 8 It is apparent that neurogranin can predict cognitive decline and neurodegeneration; however, such exemplary studies have focused on CSF content.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 87%